Antibody and B-cell responses may control circulating lipopolysaccharide in patients with HIV infection - Lim, A.; Amini, A.; D'Orsogna, L.J.; Rajasuriar, R.; Kramski, M.; Lewin, S.R.; Purcell, D.F.; Price, P.; French, M.A. (Lippincott Williams & Wilkins, 2011)
OBJECTIVES: To examine the relationship between plasma markers of microbial translocation and antibodies to lipopolysaccharide (LPS) and circulating memory B cells in patients with HIV infection.